Odpowiedzi

2009-12-19T21:20:26+01:00
A)3x - 2y = 0
2y = 3x-0
6y - 10x - 4 = 0
3(3x - 0) - 10x - 4 = 0

b)2x - y = 16
y = 2x - 16
(x(x + 1) - (x + 2)² = 2x - 16 - 3
(x + 1 + x²) - x² + 4 = 2x - 19
x - 3 = 2x - 19
x - 2x = -19 + 3
-x = -16
x = 16
y = 32 - 16 = 16
2009-12-19T21:27:22+01:00
A)
3x - 2y = 0
6y - 10x - 4 = 0

3x - 2y = 0
3x = 2y
x = (2/3)y

6y - 10*(2/3) = 4
6y - 10*(2/3) = 4
6y=14*(2/3)
y = 44/18
y = 22/9
x = (2/3) * (22/9) = 44/27

b)
x(x+1)-(x+2)²=y-3
½x-¼y=4

2x - y = 16
y = 16 - 2x

x(x+1)-(x+2)^2=16-2x-3
x^2+x-x^2-4x-4=13-2x
-5x+2x=17
3x=-17
x=-(17/3)
y=16-2*(-[17/3])
y=16+(34/3)
y=16+11*(1/3)
y=37*(1/3)